Determinants of antenatal care utilization in India: a spatial evaluation of evidence for public health reforms. (January 2019) - John, A.E.; Nilima,; Binu, V.S.; Unnikrishnan, B.
Abstract: Objective: The objective is to examine the spatial variations and to identify the determinants of antenatal care (ANC) utilization while controlling for the spatial dependence in the data. Study design: This is an ecological study on ANC utilization data from District Level Household Survey-4 (2012–2013) in India. Methods: A secondary data analysis was performed on the derived data. The unit of analysis in this ecological study was 275 districts from 20 states of India. The study comprises ever married women of reproductive age. Determinants of ANC utilization were obtained using ordinary least square (OLS), spatial lag, and spatial error models. Model adequacy check was performed using the Akaike information criterion, R-squared, log likelihood, and Schwarz criterion. The software used is GeoDa and Quantum Geographic Information System. Results: The presence of spatial autocorrelation (Moron's I = 0.6210) enforces the usage of geographic properties while modeling. The geographic clustering of low-rate districts was observed in states in Northeast India. In the present study, the model adequacy check reveals that the spatial error model performs better than the spatial lag and OLS models. The spatial pattern of the percentage of pregnant women with full ANC was observed to be associated with literacy ( P  = 0.04), birth order ( P  < 0.001), Janani Suraksha Yojana beneficiaries ( P  = 0.048), and availability of health infrastructure, staff, and services ( P  = 0.023). Conclusions: The present study findings provide valuable insights into factors affecting ANC utilization. In addition to available ANC services, customized safe motherhood interventions and region-specific awareness programs would enhance the utilization, ensuring better maternal and child health. Highlights: Customized safe motherhood intervention. Need based awareness program. Accessibility of health facility need to be reviewed.